Health Literacy in Pediatric Consultations on Allergy Prevention - Julia von Sommoggy; Eva-Maria Skiba; Jonas Lander; Christian Apfelbacher; Janina Curbach; Susanne Brandstetter (SLACK Incorporated, 2024)
Background: The first 3 years of life offer an opportunity to prevent allergic diseases. Pediatricians are an important source of health information for parents. However, a certain degree of health literacy is necessary to understand, appraise, and apply preventive behavior, which can be supported by health literacy (HL) sensitive consultations and a HL friendly environment. Objective: In this study, we want to shed light on how pediatricians in outpatient care in Germany advise on early childhood allergy prevention (ECAP) and how they consider parental HL. Methods: We conducted 19 semi-standardized telephone interviews with pediatricians from North-Rhine-Westphalia and Bavaria. The interviews were audio-recorded, transcribed, pseudonymized, and subjected to content analysis. Key Results: Current ECAP recommendations were well known among our sample. Despite the shift of evidence from avoidance of allergens toward early exposure, providing advice on ECAP was considered non-controversial and it was widely assumed that recommendations were easy to understand and apply for parents. However, ECAP was treated as an implicit topic resonating among others like infant nutrition and hygiene. Regarding HL, our interview partners were not aware of HL as a concept. However, they deemed it necessary to somehow assess parental information level and ability to understand provided information. Formal HL screening was not applied, but implicit strategies based on intuition and experience. Concerning effective HL-sensitive communication techniques, interviewees named the adaptation of language and visual support of explanations. More advanced techniques like Teach Back were considered too time-consuming. Medical assistants were considered important in providing an HL-sensitive environment. Time constraints and the high amount of information were considered major barriers regarding HL-sensitive ECAP counseling. Conclusion: It seems warranted to enhance professional education and training for pediatricians in HL and HL-sensitive communication, to reach all parents with HL-sensitive ECAP counseling. [HLRP: Health Literacy Research and Practice. 2024;8(2):e47-e61.]